2011
DOI: 10.1021/bi201181q
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of Structure and Function in the Haloacid Dehalogenase Enzyme Superfamily: Bacteroides thetaiotaomicron BT2127 Is an Inorganic Pyrophosphatase

Abstract: The explosion of protein sequence information requires that current strategies for function assignment must evolve to complement experimental approaches with computationally-based function prediction. This necessitates the development of strategies based on the identification of sequence markers in the form of specificity determinants and a more informed definition of orthologues. Herein, we have undertaken the function assignment of the unknown Haloalkanoate Dehalogenase superfamily member BT2127 (Uniprot acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…However, a sampling of k cat /K m values from this analysis ( (20,(22)(23)(24), similar to those of C1 and C2 enzymes (21,22,(25)(26)(27). Overall, the finding that C0 members, which have the most minimal cap inserts, are equally efficient and more specific than the other subfamilies suggests that incorporation of additional domains leads to the expansion of the substrate repertoire in the HADSF.…”
Section: Resultsmentioning
confidence: 58%
“…However, a sampling of k cat /K m values from this analysis ( (20,(22)(23)(24), similar to those of C1 and C2 enzymes (21,22,(25)(26)(27). Overall, the finding that C0 members, which have the most minimal cap inserts, are equally efficient and more specific than the other subfamilies suggests that incorporation of additional domains leads to the expansion of the substrate repertoire in the HADSF.…”
Section: Resultsmentioning
confidence: 58%
“…Sequenced genomes containing membrane PPases additionally include genes for soluble PPases, which catalyze energy-dissipating hydrolysis of PP i . Soluble PPase belonging to any of its three unrelated families (57,58) Second, experiments with the photosynthetic bacterium R. rubrum indicated that the H ϩ -PPase gene is expressed throughout all growth phases under anaerobic conditions (60), but its expression level declines progressively in the transition to aerobic conditions in both photosynthetic and fermentative cultures but again increases upon exposure to salt (5,60). Similarly, exposure of plants to anoxia, cold, drought, salt, or nutrient limitation increases the abundance and activity of H ϩ -PPase (61)(62)(63)(64)(65).…”
Section: Why Do Cells Need Membrane Ppases?mentioning
confidence: 99%
“…HAD superfamily members, in general, are known to act on a wide range of substrates. There are ample examples in literature showing the broad substrate and co-factor specificity of HAD superfamily members (Lu et al, 2005;Nguyen et al, 2008;Huang et al, 2011;Lu et al, 2011). In one study on a HAD superfamily member, BT4131, it was shown that the enzyme can utilize several divalent metal-ion cofactors and different sugar phosphates as substrates with varying kcat and Km values (Lu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In yet another paper on HAD phosphohydrolase BT1666, it has been shown that the enzyme possesses broad and overlapping substrate specificity with BT4131 (Lu et al, 2011). A recent paper on understanding the substrate specificity of a HAD superfamily member from Bacteroides thetaiotaomicron (BT2127) resorted to structure determination, substrate screen and site-directed mutagenesis to show that the protein functions as an inorganic pyrophosphatase and also assists in protein synthesis by removal of the product pyrophosphate from tRNA synthase (Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%